The Effect of Performance Allowance on Employee Performance through Work Engagement as an Intervening Variable at the Banjarmasin State Polytechnic - Verry Freddy; Trisylvana Azwari; Suyatno Suyatno; Novi Shintia (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This study aims to identify and evaluate employee performance (Y) as the dependent variable and performance allowance (X) as the independent variable at the Banjarmasin State Polytechnic. Employee performance is influenced by work engagement (Z) as an intervening variable. The research employs a quantitative approach, with a sample of 94 employees from Poliban, selected through random sampling. The sample size was determined using Slovin's formula. A Likert scale, ranging from 1 to 5, was used to measure the variables in this study. Path analysis and multiple linear regression were applied to examine the relationships between variables X, Z, and Y. Data were processed using SPSS 25. The study findings reveal four key results: (1) work engagement has a positive and significant direct effect on employee performance; (2) performance allowance has a positive and significant direct effect on work engagement; (3) work engagement positively and significantly mediates the relationship between performance allowance and employee performance; (4) work engagement plays a key role in enhancing employee performance through its mediating effect.